MISKONSEPSI MAHASISWA MENGENAI IKATAN ION DALAM SENYAWA NaCl - Arif - Yasthophi; Pangoloan Soleman Ritonga (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2017)
Research on new university student misconceptions about bond in NaCl compounds has been done to identify possible misconceptions. Student misconceptions are observed using a misconception analysis instrument consisting of statements accompanied by right and wrong choices and open reasons. Based on the analysis of the instrument that has been done found that the students experience the concept of ionic bonding in the compound NaCl. Students experience misconceptions why NaCl is an ionic compound. In addition, misconceptions are also found about the physical properties of the associated NaCl compounds, ie students believe that NaCl is a compound with a brittle bond and no breaking of bonds in NaCl solution and NaCl has electrolyte properties in solid phase.